Preparation and characterization of fly ash-metakaolin based geopolymeric foaming materials - Liu Ruiping; Wang Hui; Guo Fei; Dong Yue (矿业科学学报, 2019)
The alkali activated fly ash-metakaolin based geopolymeric foaming materials were prepared at low temperature by use of fly ash,metakaolin,sodium hydroxide,sodium silicate as the main raw material.The effect of the types and contents of foaming agent on the pore structure and properties of the porous geopolymer were studied,and the thermal stability and structure were also investigated. Compared to the aluminum and sodium borate,the foaming effect of hydrogen peroxide was better.The properties of geopolymeric foaming materials prepared in ths paper were with bulk density of 0.985 g/cm3,compressive strength of 8.9 MPa,lowest thermal conductivity of 0.10 W/ (m·K) and good thermal insulation effect,when the content of hydrogen peroxide was 0.5%,the conservation temperature was 40 ℃,conservation humidity was 70% and conservation time was 7 d.